Who has the right to speak? The role of social media in spreading dissent among anti-nuclear groups in post 3-11Japan - Tamura, Takanori; Hamada, Tadahisa (AoIR Selected Papers of Internet Research, 2013)
Although much previous research (for example regarding the “Arab Spring” of 2010) has stressed the galvanizing role played by social media in the development of social activism, in this paper we show how the use of social media in Japan has actually led to a fracturing of the anti-nuclear movement following the earthquake, tsunami and nuclear accidents in Japan in March 2011. We argue that awareness of a specifically Japanese concept prioritizing the voices of those directly affected by an accident or condition, the tōjisha, has been heightened by exchanges on social media such as Twitter. We suggest that arguments among the anti-nuclear protestors on who has the most right to speak in these debates has had a debilitating effect on the anti-nuclear movement as a whole. We call for further work in Japan on the way in which social media have promoted disunity and dissent among protest groups.